Cooperation and Closure in Bilateral Trade Negotiations - Larry Crump (University of Duisburg-Essen, Käte Hamburger Kolleg / Centre for Global Cooperation Research (KHK/GCR21), 2017)
Little is known about cooperation between nations engaged in a regional economic association. This study investigates cooperation and closure between Asia-Pacific Economic Cooperation (APEC) member economies engaged in negotiating five bilateral free trade agreements (FTA), including the Australia-Singapore FTA 2003, United States-Singapore FTA 2003, Chile-United States FTA 2003, Australia-United States FTA 2004, and Korea-Australia FTA 2014. This study found that a number of factors bring about or interfere with cooperation at the closure stage. Negotiation closure occurs within FTAs when discussions shift from trade diplomats focused on technical matters to senior national leaders focused on political decisions. Creditable deadline, party stability and instability, and linkage dynamics were also found to support or interfere with cooperation at the closure stage in FTA negotiations. Often FTA negotiations are concluded on the sidelines of meetings sponsored by international organizations including APEC Leaders' Summit and Ministerial meetings.
urn:nbn:de:hbz:464-20170314-085926-9
Keywords: 320; Cooperation and closure; bilateral negotiation; free trade agreements (FTA); Asia Pacific Economic Cooperation (APEC)